2012
DOI: 10.1038/nature11032
|View full text |Cite
|
Sign up to set email alerts
|

Deformation cycles of subduction earthquakes in a viscoelastic Earth

Abstract: Subduction zones produce the largest earthquakes. Over the past two decades, space geodesy has revolutionized our view of crustal deformation between consecutive earthquakes. The short time span of modern measurements necessitates comparative studies of subduction zones that are at different stages of the deformation cycle. Piecing together geodetic 'snapshots' from different subduction zones leads to a unifying picture in which the deformation is controlled by both the short-term (years) and long-term (decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
459
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(487 citation statements)
references
References 54 publications
26
459
2
Order By: Relevance
“…Because the former is fairly uniform in NE Japan, faster velocity would reflect stronger coupling. Occasional interplate earthquakes let these points jump trenchward, often followed by slow trenchward movements lasting for years or decades caused by afterslip and viscous relaxation (Wang et al, 2012). We divide the plate boundary in NE Japan into four segments, from north to south, 1: Nemuro-Oki (this implies "off the coast of Nemuro"), 2: Tokachi-Oki, 3: Aomori-Oki (including northern Iwate-Oki), and 4: Tohoku-Oki (composed of southern Iwate-Oki, Miyagi-Oki and Fukushima-Oki).…”
Section: Decoupling In the Tokachi-oki And Tohoku-oki Segmentsmentioning
confidence: 99%
“…Because the former is fairly uniform in NE Japan, faster velocity would reflect stronger coupling. Occasional interplate earthquakes let these points jump trenchward, often followed by slow trenchward movements lasting for years or decades caused by afterslip and viscous relaxation (Wang et al, 2012). We divide the plate boundary in NE Japan into four segments, from north to south, 1: Nemuro-Oki (this implies "off the coast of Nemuro"), 2: Tokachi-Oki, 3: Aomori-Oki (including northern Iwate-Oki), and 4: Tohoku-Oki (composed of southern Iwate-Oki, Miyagi-Oki and Fukushima-Oki).…”
Section: Decoupling In the Tokachi-oki And Tohoku-oki Segmentsmentioning
confidence: 99%
“…The afterslip is the continuous slip of the fault after the main shock and is often considered downdip of the fault rupture zone (Wang et al, 2012)� We use a dislocation model with layered structures to investigate the afterslip distribution by inverting the geodetic data� We modify the fault geometry proposed by Shen et al (2009) The afterslip model can explain the postseismic displacement in the near field but there is larger misfit in the far field� On the other hand, the viscoelastic relaxation model can explain the far field postseismic displacement better than the near field� It appears that a single mechanism cannot solely explain the postseismic displacement� A multiple mechanism model is needed to fit both near, and far field displacements� We consider the 15 km thick LCF to be the main mechanism of the far field displacement, so the afterslip model may explain the misfit of the LCF model� The inversion (the 2 nd afterslip model in the lower right in Fig� 2�12�1) of the LCF residual displacement shows a significant reduction of the deep afterslip� As a result, the afterslip alone model requires more than 45 cm slip in the first year below Tibet's Moho that may already undergo ductile deformation, whereas the viscoelastic relaxation in a 15 km thick LCF can explain the GPS measurements� Consequently, the result of the Wenchuan postseismic displacement supports a weak lower crustal flow underneath eastern Tibet� Figure 2�12�1: The 3D representation of the rheologic model in eastern Tibet and western Sichuan basin� These two geologic structures are separated by the Longmen Shan� The co-and postseismic GPS displacements are shown in the black and red arrows, respectively� The two possible mechanisms of the postseismic deformation are: (1) deep afterslip (the light blue region), and (2) lower crustal flow (the purple layer)� The coseismic slip is inverted from the coseismic GPS measurements� In the lower left, the postseisic displacement during the first year is compared with the two end-member mechanisms� The two afterslip models in the lower right are inverted from the one year postseismic GPS measurements and from the LCF model residual, respectively� The deep afterslip in the multiple mechanism model is largely reduced (see text)�…”
Section: Model Of the Postseismic Displacementmentioning
confidence: 99%
“…The fundamental geological structure and rheology of the Tibetan plateau have been debated for decades� Two major models have been proposed: (1) the deformation in Tibet is distributed, and associated with ductile flow in the mantle or lower crustal flow (LCF); (2) the Tibetan plateau was formed during interactions among rigid blocks with localization of deformation along major faults� On 12 May, 2008, a M w 7�9 earthquake occurred on the Longmen Shan that separates the eastern Tibetan plateau and the Sichuan basin� The earthquake ruptured ~235 km of the Beichuan fault (BCF) and the entire Pengguan fault (PGF) (Shen et al, 2009)� Geodetic inversions show more than 5 slip asperities and ~16 m peak slip on SW BCF (Fig� 2�12�1)� All of the slip models show oblique thrusting along the SW BCF and a right-slip component gradually increases towards the NE end of the BCF� The postseismic displacement is a response to the redistribution of stresses induced by the earthquake and can be used to probe the deep rheologic properties underneath the surface (Wang et al, 2012)� Here we incorporate two-year long geodetic measurements and numerical modeling to examine two end-member hypotheses to provide further evidence to the deep rheology in eastern Tibetan plateau�…”
Section: Introductionmentioning
confidence: 99%
“…For deeper events it has been suggested that the plate interface may recover its interseismic locked state rapidly, as, for example, after the Pisco 2007 M w 8.0 and Tocopilla 2007 M w 7.8 events [Remy et al, 2016;Weiss et al, 2016]. Recent observations following the Valdivia 1960 M w 9.5 and Maule 2010 M w 8.8 megathrust earthquakes suggest that the relocking process may be heterogeneous in space and time [Moreno et al, 2011;Métois et al, 2012] and accompanied by a prolonged phase of postseismic relaxation of the mantle [see, e.g., Wang et al, 2012;Ruiz et al, 2016, Bedford et al, 2016Klein et al, 2016]. Therefore, to characterize the first indications of the seismic reawakening after the Valdivia megathrust earthquake and its associated lag time, it is essential to improve the understanding of the recurrence of earthquakes in the plate interface.…”
Section: Introductionmentioning
confidence: 99%